Peran Polri dalam Mendukung Pemulihan dan Percepatan Ekonomi Nasional Tahun 2024 - Sutrasno, Dadang; Rizki Saputra; Ajeng Hananingrum (Pusat Penelitian dan Pengembangan Polri, 2025)
The COVID-19 pandemic has led to a global economic decline, with economic growth decreasing by 5.2% (World Bank, 2020). The efforts of the Indonesian National Police (Polri) in maintaining security and public order have indirectly contributed to the economic stability. The Research and Development Center of Polri conducted a study on Polri’s role in supporting the national economic recovery and acceleration. This study used mixed-method approach. The quantitative analysis was using the Analytical Hierarchy Process and the qualitative analysis was using Focus Group Discussions. Secondary data was obtained from BPS (Statistics Indonesia), Polri's internal sources, and other documents related to Polri's policies and government policies. Primary data was collected through observations, interviews, discussions, and surveys. The results are: 1) The implementation of activities in each operational function has not yet been directed towards enhancing the economy. 2) Public expectations revealed that 46.76% of respondents believed that the relationship between public security and economic recovery is progressing in line with the challenges, which have been addressed. 3) The Police’s involvement in economic recovery and acceleration requires coordination and collaboration, both within operational functions and with stakeholders. 4) The police's involvement in economic recovery and acceleration should be complemented by improvements in the capacity and capability of its personnel. Challenges requiring active police involvement include: 1) Ensuring a sense of security in economic activities. 2) Economic recovery and acceleration in certain regions indicate challenges such as potential security disturbances caused by youth unemployment.